From Boom to Bust : John E. Burton and the Northern Wisconsin Iron Mines, 1885-1887 - Krezoski, Gillian M. (My University, 2007)
Since the industrial revolution, occurring prior to the turn of the 19th century, the United States has had a fascination with iron. Iron ore is a main component of steel, which built transportation systems, cities, and even empires. This paper studies one man, John E. Burton, who was involved in the Gogebic Range in northern Wisconsin. This writing argues that this man was a major influence in bringing investors, tourists, and money to northern Wisconsin. This, in turn, helped to speed the development of the northern part of the state. Railroads cut through the wilderness and shipping yards were built on Lake Superior. Overall, John Burton was a small-scale iron baron who entered the market at the wrong time. His vision was to be a success on a small scale, while the nation was looking to the start of corporations to supply large-scale needs. Burton, though not successful as an iron baron, still played an integral part in shaping the history of northern Wisconsin.
Keywords: Iron mines and mining--Gogebic Range (Mich. and Wis.)--History; Economic development--Superior, Lake, Region--History; Burton, John E. (John Edgar), b. 1847; Gogebic Range (Mich. and Wis.)--History; Iron miners--Gogebic Range (Mich. and Wis.)--Biography